2009
DOI: 10.1007/s10452-009-9230-2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of amphipod assemblages associated with Sargassum filipendula (Phaeophyta) and its epiphytes in a subtropical shore

Abstract: The phytal assemblages change in response to variation in biological and environmental conditions. In the present study, we evaluated the temporal variation of amphipod assemblages associated with a Sargassum filipendula bed in a subtropical shore, in relation to variation of the host alga, its epiphytes and local environmental conditions. Samples of S. filipendula with associated amphipods, water temperature, water movement and suspended solids were obtained monthly from June 2000 to May 2001. We recorded 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
29

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 34 publications
3
41
0
29
Order By: Relevance
“…Despite the limitations of this work concerning time and spatial sampling, we are confident that the results allow a consistent discussion since the families of amphipods found here are frequently associated to Sargassum in this region (Tanaka and Leite, 2003;Jacobucci et al, 2009). Moreover, considering these amphipod families have a wide distribution (Barnard and Karaman, 1991), we point out the patterns found in our study may be observed in other areas with straight thallus algae.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Despite the limitations of this work concerning time and spatial sampling, we are confident that the results allow a consistent discussion since the families of amphipods found here are frequently associated to Sargassum in this region (Tanaka and Leite, 2003;Jacobucci et al, 2009). Moreover, considering these amphipod families have a wide distribution (Barnard and Karaman, 1991), we point out the patterns found in our study may be observed in other areas with straight thallus algae.…”
Section: Discussionsupporting
confidence: 79%
“…Natural history aspects, such as behavior and feeding habits, can influence the occurrence of amphipods in macroalgae (Tanaka and Leite, 2003;Jacobucci et al, 2009). The basal portion of Sargassum may be less subject to the action of waves (Rossi et al, 2000;Fraschetti et al, 2006) and because of the proximity to the physical substrate and the weak currents, it may accumulate a larger amount of particles (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These species can show distinct frond dimensions and degree of branching depending on water movement (Paula, 1988;Széchy & Cordeiro-Marino, 1991). This structural variation can determine differences in the composition and relative abundance of epiphytic algae and of the associated epifauna (Jacobucci et al, 2009). Among the organisms of the macro-epifauna whose occurrence can be influenced by the presence of epiphytes in Sargassum fronds, there are various species of amphipods (Norton & Benson, 1983;Martin-Smith, 1993;Viejo, 1999;Leite & Turra, 2003), some of which utilize algae not only as refuge, but also as a food resource.…”
Section: Introductionmentioning
confidence: 99%